Prevalence and reasons for electronic nicotine delivery systems modifications among U.S. youth, young adult, and adult users - Lucy Popova; Bai Cham; Zachary B. Massey; Thi Phuong Thao Tran; Mohammed M. Alqahtani; Robert T. Fairman; Ruiyan Luo; Scott R. Weaver; David L. Ashley (Scientific Reports)
Abstract This study evaluated the prevalence of various electronic nicotine delivery systems (ENDS) modifications among U.S. ENDS users and reasons for these modifications. We conducted a national survey of U.S. youth (13–17 years old, n = 553), young adults (18–29 years old, n = 634), and older adults (30 + , n = 760) who reported past 30-day ENDS use in 2021. The result showed that, in each age group, a large majority had engaged in at least one ENDS modification (youth, young adults, and older adults respectively: 84.3%, 84.1%, 76.9%), with modifications to e-liquid (68.1%, 61.2%, 48.7%) and coils (63.7%, 61.4%, 57.2%) being the most common. For some modifications, prevalence varied by age group and race/ethnicity. Participants endorsed various reasons for modifications, many related to accessing or enhancing the flavor of the aerosol. For youth, having heard about the modification was an important reason for trying a modification. Conversely, young adults and older adults frequently mentioned making the device last longer and saving money. ENDS modifications are widespread, but the reasons for modification differ between age groups. Some of these common modifications can lead to potential harm; they need to be regulated through product standards and marketing decisions, and ENDS users should be educated about potentially dangerous modifications.